Motor Learning Deficits in a Neonatal Mouse Model of Hypoxic-Ischemic Injury - Maria Marlicz; Weronika Matysik; Emily Zucker; Sarah Lee; Hannah Mulhern; Jennifer Burnsed (Children)
Background/Objectives: Motor deficits following neonatal brain injury, from cerebral palsy to subtle deficits in motor planning, are common yet underreported. Rodent models of motor deficits in neonatal hypoxia–ischemia (HI) allow improved understanding of the underlying mechanisms and neuroprotective strategies. Our goal was to test motor performance and learning in a mouse model of neonatal HI. Methods: We induced HI in postnatal day (p)10 C57/Bl6 mice through unilateral carotid ligation followed by 60 min of 8% oxygen exposure, or a sham procedure. At p30, we assessed complex motor performance and learning using the accelerating rotarod and complex running wheel tasks. Results: In the rotarod task, HI mice performed worse than sham mice, with shorter latencies to fall (n = 6 sham, 9 HI; day 1, p = 0.033; day 2, p = 0.013; day 3, p = 0.023). Sham mice demonstrated improved performance across days (p = 0.005), and HI mice did not (p = 0.44). During the simple running wheel task, we observed no difference in wheel rotation and speed between groups (n = 5/group; day 1, p = 0.67; day 4, p = 0.53). However, when navigating a wheel with a random pattern of spokes removed (complex task), HI mice took longer than sham mice to reach a plateau in performance (n = 5/group; day 1, p = 0.02; day 4, p = 0.77). Conclusions: Our findings demonstrate that young adult mice exposed to HI exhibit significant deficits and delayed learning in complex motor performance compared to sham mice. HI mice do not show deficits in gross motor performance; however, more subtle impairments are present in complex motor performance and learning. This HI model exhibits subtle motor deficits relevant to findings in humans and may be a useful tool in testing further neuroprotective strategies.